Radio Frequency Multiple Access Techniques Made Easy - Faruque, Saleh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive overview of multiple access techniques used in the cellular industry. The usage of multiple access techniques in telecommunications enables many users to share the same spectrum in the frequency domain, time domain, code domain or phase domain. Licenses are given, by the FCC, to operate wireless communication systems over given bands of frequencies, with the smaller bands, (channels), reused to provide services to other users. Thus, bandwidth efficiency is vital, as the speed and size of digital data networks continue to expand. This brief also uses numerous illustrations to bring students up-to-date in the practical applications of multiple access techniques, which can then be put to work in the industry. Primarily, electrical engineering students who study telecommunications, as well as engineers and designers working in wireless communications, would find this book useful.
Introduction -- Simplex, Duplex, FDD & TDD -- Frequency Division Multiple Access (FDMA) -- Time Division Multiple Access (TDMA) -- Code Division Multiple Access (CDMA) -- Code Division Parallel Access (CDPA) -- Orthogonal Frequency Division Multiple Access (OFDMA) -- .
Keywords: Telecommunication; Computer networks .; Electronics; Communications Engineering, Networks; Computer Communication Networks; Electronics and Microelectronics, Instrumentation